A hierarchical porous Fe-N impregnated carbon-graphene hybrid for high-performance oxygen reduction reaction. (April 2019) - Wang, Sihui; Yan, Xiao; Wu, Kuang-Hsu; Chen, Xuemin; Feng, Jian-Min; Lu, Pengyi; Feng, Hou; Cheng, Hui-Ming; Liang, Ji; Dou, Shi Xue
Abstract: A Fe-N impregnated carbon in a hybrid with in-situ grown graphene from hierarchical porous carbon has been obtained for high-performance oxygen reduction reaction (ORR) catalysis. This hybrid material combines the desirable characteristics for the ORR, including Fe-N active sites, high surface area, good electron conductivity, and hierarchical channels for mass diffusion. As a result, this catalyst exhibits a very positive reaction onset potential (−0.05 V vs. Ag/AgCl), a high ORR current density, and a complete four-electron ORR pathway, which are even better than a commercial 20% Pt/C catalyst. We further reveal the synergistic ORR enhancement from the controlled Fe-N impregnation in the doped carbon-graphene hybrid. Graphical abstract: A hierarchical porous Fe-N impregnated carbon-graphite has been obtained, which carries outstanding ORR catalytic capability even better than the state-of-the-art Pt/C catalyst in an alkaline electrolyte. The excellent performance of this hybrid material can be attributed to the Fe-N active sites, high surface area, good electron conductivity, and hierarchical channels for facile mass diffusion. Image 1